The effect of using competencies on selection and appointment policies in the Palestinian Ministry of Higher Education and Scientific Research (Normative Commitment, variable and mediating) - Al-Tamiza, Khaled Musa (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed at trying to build and test the validity of a theoretical model to reveal the effect of using the competency framework on selection and appointment policies in the Ministry of Higher Education and Scientific Research in Palestine in light of the mediating role of the standard commitment variable. To achieve this purpose, the researcher used the descriptive and analytical method and the questionnaire to collect data from a sample of (223) employees, And to test the study hypotheses related to studying the direct and indirect impact of using the competency framework on selection and appointment policies, Partial Least Square Structural Equation Modeling was used based on Smart PLS 3.2.1 program, and the theoretical framework of the study is based on theory Evaluate the application of competencies according to the Holistic competence model presented by (Porvaznik, J a Kol, 2013), which consists of three dimensions (the cognitive dimension, the application dimension, and the social dimension), while the researcher added the technical dimension to suit the purposes of the study and cover all its aspects. The results of the study indicated that the degree of availability of competencies in its various dimensions was high, as the mean value for them was (3.71), The results showed that the highest degree of availability of competencies is on the dimension of social maturity skills, where the value of the arithmetic average was (3.90), while the lowest was the application skills, where the value of the arithmetic mean was (3.55). The results also showed that there is a direct positive impact of cognitive abilities on selection and appointment policies. And the designation (0.179) while there was no statistically significant direct effect for the other dimensions, and it was also found that there was a positive effect of the dimensions of cognitive and applied competencies and social maturity on the standard commitment of workers (0.159, 0.391, 0.152, respectively), and the results also showed that the standard commitment partially mediates The relationship between cognitive abilities and selection and recruitment policies (0.062), The results also showed that the standard commitment mediates the relationship between application skills and the selection and appointment policies (0.152). The study recommended the necessity of addressing the problems of using competencies and building a comprehensive strategy to implement the competency framework in the various practices entrusted with managing human resources in the Palestinian civil service, to be the beginning of a stepping-stone towards promoting the transition to competency-based human resource management.